EUROPEAN PRIORITIES FOR PERSONAL INCOME TAXATION - TKACHYK, Fedir; OSTAPCHUK, Victoriia (Scientific journal «World of Finance», 2020)
Introduction. In the current conditions of globalization of socio-economic development and formation of a new financial civilization, social aspects of tax policy take a important place. The system of taxation of income of citizens in Ukraine today is not fully coping with the performance of their functions. The experience of developed European countries on the formation of an effective mechanism of taxation of personal income will contribute to the establishment of the newest social and fiscal-oriented paradigm of taxation of citizens in Ukraine. The increased interest in the procedures for administering the personal income tax is also explained by the fact that this tax is one of the main sources of income to the budget of Ukraine. The purpose is to determine the peculiarities of taxation of personal income tax in Ukraine, to find out the common and different features tax system in Ukraine and European countries, to systematize recommendations on improving the mechanism of taxation of personal income. Results. The international typology of personal income tax systems is given. The general features of personal income taxation and mechanisms of application of personal income tax rates in some countries of the European Union are considered. It is argued that the implementation of the European tax experience will facilitate a faster transition to a new and effective system of personal income taxation in Ukraine. To improve personal income taxation in Ukraine, it is necessary to revise personal income tax rates, increase the amount of tax-free minimum incomes, ensure the full functioning of electronic declaration of personal incomes, optimize concessional policies, increase tax literacy and tax culture. Prospects. Further research will focus on the social aspects of taxing citizens’ income in terms of differentiation of tax rates, the logic of using preferences in taxing personal income, the introduction of an effective threshold of the non-taxable minimum income, promoting the right to tax rebates, etc.